Philanthropy from the perspective of the holy Quran: A case study among Muslim community in Gansu province, China / Mao Zhan Qin - Mao, Zhan Qin (2020)
It is Allah s commands being the main motivation and reason for people to seek philanthropy according to Islamic sharia. The study aims at clarifying the conceptual and jurisprudential framework of philanthropy by among the Mu Jim Community in Gansu Province in China. The theoretical par1 of this study was based on the descriptive and historical approaches, while the empirical side is based on analytical approach. This was done by using questionnaire as a research instrument through which data was collected by targeting a sample of those engaged in charitable work in the charities and centres in Gansu. The study concluded that charity work in China in general widespread, and within the Muslim community in Gansu in particular where developmental and social role of many charities and centres spread. This role has nothing to do with the role of preachers. The study also concluded that in institution and charities have little awareness concerning the fiqh (jurisprudence) of charitable work. Furthermore, the study concludes that charities and centres face number of challenges, the most important of which are the fear of partisan and sectarian affiliations the authorities fear of extremism and terrorism the influence of religion and philosophical ideas of understanding religion, the multiplicity of Islamic references and sect well as the bureaucracy or foundational and organizational procedures. The researcher recommends that in order to promote charitable work based on sharia and the rule fit fiqh, it is necessary to spread the fiqh of charitable work and unite the efforts to Muslim scholar in China under the Association of Ulema Uniting Islamic References. It is also to qualify imams and preachers in order to spread awareness within the community in the spirit of the time